Uterine conserving surgery in a case of cervicovaginal agenesis with cloacal malformation - Mishra, Vineet; Saini, Suwa Ram; Roy, Priyankur; Aggarwal, Rohina; Verneker, Ruchika; Hokabaj, Shaheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cervico-vaginal agenesis (MRKHS) with normally formed uterus along with cloacal malformation is a very rare mullerian anomaly. We report a case, of a 13-year-old girl who was admitted at our tertiary care center with complaints of primary amenorrhea and cyclical lower abdominal pain for 3 months. Clinical examination and radiological investigations revealed complete cervico-vaginal agenesis with normal uterus with hematometra with horse shoe kidney. Vaginoplasty was done by McIndoe’s method with uterovaginal anastomosis and neocervix formation. Malecot’s catheter was inserted in uterine cavity. Vaginal mould was kept in the neovagina. Mould was removed after 10 days under anaesthesia and repeat hysteroscopy with insertion of a small piece of malecot’s catheter was performed under hysteroscopic guidance into the uterine cavity through neocervix and lower end fixed to the vagina. After 3 months, the malecot’s catheter was removed. During follow up, she was menstruating normally at 6 months post-operatively and had a completely healed vaginal mucosa. Earlier hysterectomy was considered as a definitive surgery for this condition; however, it has been replaced with more conservative approach, like uterovaginal anastomosis with creation of neovagina. In literature, successful pregnancy has been reported in these patients who underwent conservative surgery.